2011
DOI: 10.1007/s00267-011-9801-6
|View full text |Cite
|
Sign up to set email alerts
|

A Framework for Assessing Collaborative Capacity in Community-Based Public Forest Management

Abstract: Community-based collaborative groups involved in public natural resource management are assuming greater roles in planning, project implementation, and monitoring. This entails the capacity of collaborative groups to develop and sustain new organizational structures, processes, and strategies, yet there is a lack of understanding what constitutes collaborative capacity. In this paper, we present a framework for assessing collaborative capacities associated with community-based public forest management in the U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(45 citation statements)
references
References 36 publications
0
42
0
3
Order By: Relevance
“…Koontz et al (2004) suggest that ''collaborative environmental management offers a flexible approach that can be molded in response to emerging views and knowledge.'' Despite such claims, however, the collaborative governance literature and associated scholarship on collaborative capacity has not focused particularly on adaptive qualities or capacities per se nor has it demonstrated that collaborative governance indeed cultivates such capacities (Cheng and Sturtevant 2012). Furthermore, in most frameworks for collaborative governance, performance outcomes are given short shrift and there is little, if any, treatment of feedback or collective learning that might occasion opportunities for or demonstrate adaptation (Koontz and Thomas 2006;see Gerlak and Heikkila 2011;Cheng and Sturtevant 2012 as exceptions).…”
Section: Collaborative Governancementioning
confidence: 99%
“…Koontz et al (2004) suggest that ''collaborative environmental management offers a flexible approach that can be molded in response to emerging views and knowledge.'' Despite such claims, however, the collaborative governance literature and associated scholarship on collaborative capacity has not focused particularly on adaptive qualities or capacities per se nor has it demonstrated that collaborative governance indeed cultivates such capacities (Cheng and Sturtevant 2012). Furthermore, in most frameworks for collaborative governance, performance outcomes are given short shrift and there is little, if any, treatment of feedback or collective learning that might occasion opportunities for or demonstrate adaptation (Koontz and Thomas 2006;see Gerlak and Heikkila 2011;Cheng and Sturtevant 2012 as exceptions).…”
Section: Collaborative Governancementioning
confidence: 99%
“…During times of "crisis, breakdown, and reorganization"-which would include the aftermath of unusually large and severe wildfires-resilience theory suggests that moving beyond conventional decision support systems to decentralized, participatory, and collaborative approaches can help build adaptive capacity , Walker et al 2002. Cheng and Sturtevant (2012) propose a framework for assessing the collaborative capacity of communities in the context of federal forest management. Their framework identifies six arenas of collaboration and associated capacities: organizing, learning, deciding, acting, evaluating, and legitimizing.…”
Section: Collaboration In National Forest Managementmentioning
confidence: 99%
“…Building on these advantages, community-based voluntary participation in ecological restoration (conservation) has shown global growth [10][11][12].…”
Section: Introductionmentioning
confidence: 99%